EFEKTIVITAS PENGGUNAAN APLIKASI JAMSOSTEK MOBILE (JMO) DALAM MENINGKATKAN PELAYANAN BAGI PESERTA JAMINAN SOSIAL TENAGA KERJA DI KABUPATEN BANDUNG TAHUN 2023 - Naya Putri Pradiya; Rudiana Rudiana; Yayan Nuryanto (T JDP (JURNAL DINAMIKA PEMERINTAHAN), 2024)
BPJS Ketenagakerjaan has developed the Social Security Manpower Mobile (JMO) application as an innovation in services to labor social security participants. Therefore, this study will discuss the effectiveness of using the JMO application in improving services for labor social security participants in Bandung Regency in 2023. This study uses a qualitative method to analyze the effectiveness of the JMO application service based on a process approach, a source approach, and a target approach. The data collection techniques of this study include observation, interviews, and documentation. Data collection techniques in this study include observation, interviews, and documentation. The results showed that services through the JMO application in Bandung Regency still face obstacles in organizing socialization to the community. Consequently, the use of the JMO application by labor social security participants in Bandung Regency has not been fully optimized.